‘There was no freedom to leave’: Global South international students in Portugal during the COVID-19 Pandemic - Malet Calvo, D.; Cairns, D.; França, T.; Azevedo, L. F. de (Policy Futures in Education, 2022)
This article looks at the impact of the COVID-19 pandemic on international students, focusing on Portuguese-speaking African and Brazilian students during the lockdown of spring 2020. Using evidence from interviews conducted with 27 students domiciled in Portugal, we illustrate some of the challenges faced by students when coping with the pandemic, including difficulties in meeting the cost of tertiary education and the centrality of working to sustain their stays abroad, alongside the emotional impact of prolonged domestic confinement and separation from families. We also consider the paradoxes of online teaching, which have made visible the digital gap between local and international Global South students in the context of their stays. In this sense, pre-existing inequalities are more at the centre of students’ concerns than new issues raised by COVID-19, a pandemic that served to reveal former injustice in the context of global capitalism. In our conclusion, we argue that there is a need for greater recognition of the vulnerabilities facing certain African and Brazilian students at Global North universities in the context of contemporary neoliberalism, including their dependence upon precarious work. Policy responses include the need for a more serious involvement and responsibility by both home and host higher education institutions in the lives of their students abroad.